Teachers' Attributes and Self-Efficacy as Predictors of Classroom Management - Cecilia Suico (International Journal of Asian Education, 2021)
This descriptive-correlational research examined the teachers' attributes and self-efficacy as predictors to classroom management. The study aims to help teachers, school principals, and future researchers address some classroom management gaps. This study was participated by 200 senior high school teachers of Monkayo, Davao de Oro. The instruments used in gathering the data were adopted, content validated, and reliability tested. The result showed that the extent of teachers' attributes was very great, and the level of teachers' self-efficacy was also very high. As a result, the level of classroom management of teachers was described as very high. The result further showed the significant relationship between teachers' attributes to classroom management. Lastly, this study revealed that teachers' attributes and self-efficacy significantly predict classroom management. Therefore, the study recommends that the elementary school administrators develop programs that equip teachers with the necessary attributes, skills, and passion for the teaching profession and be given more professional growth consideration